A Compact 12-Port MIMO Dielectric Lens Antenna With Wide-Angle Beam Scanning for Ka-Band Applications - Massinissa Belazzoug; Idris Messaoudene; Yassine Himeur; Boualem Hammache; Salem Titouni; Rida Gadhafi; Raouf Zerrougui; Youcef Braham Chaouche; Shadi Atalla; Wathiq Mansoor (IEEE Open Journal of the Communications Society)
This paper tackles significant challenges in the design of millimeter-wave MIMO (Multi-input Multi-output) antennas for the Ka-band (26-30 GHz) as utilized in 5G applications. Current antenna designs suffer from limitations such as constrained bandwidth, inadequate gain, and restricted beam scanning capabilities, adversely affecting performance, particularly in high-density urban environments. A novel MIMO antenna featuring a 12-port dielectric lens has been proposed to address these issues, introducing several advancements to improve key performance metrics. The antenna demonstrates a peak realized gain of approximately 14 dBi and achieves a bandwidth exceeding 4 GHz. Importantly, it features full 360° beam scanning capabilities and maintains an exceptionally low envelope correlation coefficient (ECC) of less than 0.0014. The design also shows impressive radiation efficiency consistently exceeding 95%, complemented by excellent isolation characteristics with mutual coupling maintained below −30 dB. This research provides a scalable solution that could significantly enhance the performance of next-generation wireless networks, addressing the high demands of urban 5G deployments.